Manajemen Akun Pengguna Berbasis Roaming Profile untuk Memperkuat Perlindungan Data di Laboratorium Komputer - Aditya Wahyu Firmansyah; Ronald David Marcus; Asri Samsiar Ilmananda; Fandi Yulian Pamuji (LPPM STIKI MALANG, 2022)
Roaming profile is a feature of managing user’s profile centrally through the active directory on Windows Server, which is useful to redirects all application settings and data storage to the server, so that users can access their profiles on any computer on the network. Compared to the local profile that relies on a local hard drive, a roaming profile is more suitable for user account management in a computer laboratory, because students use PCs interchangeably and move from one PC to another. This study aims to shift the local profile setting which was previously still used in the computer laboratory of the Faculty of Information Technology, Universitas Merdeka Malang, to a roaming profile-based setting. This research is expected to present a solution to make it easier for students to access their own profiles, while providing protection for the files they store. The method of this research is based on a qualitative and experimental approach. The results showed that the implementation of an active directory with a roaming profile was able to improve the quality of service in the computer laboratory, as well as increase security and convenience for students.